ANALYSIS OF THE EFFECT OF ISLAMIC COMMERCIAL BANK FINANCING AND INFLATION ON ECONOMIC GROWTH IN INDONESIA 2010-2019 PERIOD - Yola Yolanda; Amir Machmud; Nabilah Yusof (IAIN Batusangkar, 2021)
This study aims to analyze the effect of Islamic commercial bank financing on the analysis of financial development in Indonesia, and to analyze the effect of inflation on financial development in Indonesia. This research method is multivariate cointegration and error correction model (ECM). Research uses time series data using Time series data starts from 2010 to 2019 with a total of 40 data (n), the data is sourced from the financial services authority (OJK). The findings in this study indicate that Islamic commercial bank financing has a significant effect on economic growth in Indonesia. The coefficient value of -0,122 indicates that every 1% economic growth will reduce the economic growth index in Indonesia by 0.122%. Meanwhile, inflation has a positive and insignificant effect on economic growth in Indonesia. The coefficient value of 0.028 indicates that every 1% increase in inflation has no effect on the increase in the financial development index in Indonesia by 0.028%. It is fitting for the government in this case to encourage the development of Islamic banking to be proven to have contributed to economic growth through regulations that can support the acceleration of Islamic banking to the national economy